Integrin-mediated electric axon guidance underlying optic nerve formation in the embryonic chick retina - Masayuki Yamashita (Communications Biology, 2023)
Abstract Retinal ganglion cell (RGC) axons converge on the optic disc to form an optic nerve. However, the mechanism of RGC axon convergence remains elusive. In the embryonic retina, an electric field (EF) exists and this EF converges on the future optic disc. EFs have been demonstrated in vitro to orient axons toward the cathode. Here, I show that the EF directs RGC axons through integrin in an extracellular Ca2+-dependent manner. The cathodal growth of embryonic chick RGC axons, which express integrin α6β1, was enhanced by monoclonal anti-chicken integrin β1 antibodies. Mn2+ abolished these EF effects, as Mn2+ occupies the Ca2+-dependent negative regulatory site in the β1 subunit to eliminate Ca2+ inhibition. The present study proposes an integrin-mediated electric axon steering model, which involves directional Ca2+ movements and asymmetric microtubule stabilization. Since neuroepithelial cells generate EFs during neurogenesis, electric axon guidance may primarily be used in central nervous system development.